2015
DOI: 10.1017/s0007123414000556
|View full text |Cite
|
Sign up to set email alerts
|

Is Belief in Conspiracy Theories Pathological? A Survey Experiment on the Cognitive Roots of Extreme Suspicion

Abstract: What are the origins of belief in conspiracy theories? The dominant approach to studying conspiracy theories links belief to social stresses or personality type, and does not take into account the situational and fluctuating nature of attitudes. In this study, a survey experiment, subjects are presented with a mock news article designed to induce conspiracy belief. Subjects are randomly assigned three manipulations hypothesized to heighten conspiracy perceptions: a prime to induce anxiety; information about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 54 publications
5
53
1
Order By: Relevance
“…For example, people who lack agency and control may reclaim some sense of control by believing conspiracy theories because they offer the opportunity to reject official narratives and allow people to feel that they possess a better account. Consistent with this reasoning, studies have demonstrated that conspiracy beliefs are associated with feelings of powerlessness (Abalakina‐Paap et al, ; Pratt, ; Zarefsky, 1984/), anxiety (Grzesiak‐Feldman, ; Radnitz & Underwood, ), anxious attachment style (Green & Douglas, ), and existential anxiety (Newheiser, Farias, & Tausch, ). Further, Bruder et al () demonstrated a relationship between conspiracy thinking and low feelings of control in the sociopolitical domain (see also Nyhan, ; van Prooijen and Acker ; Uscinski & Parent, ).…”
Section: Definitionsmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, people who lack agency and control may reclaim some sense of control by believing conspiracy theories because they offer the opportunity to reject official narratives and allow people to feel that they possess a better account. Consistent with this reasoning, studies have demonstrated that conspiracy beliefs are associated with feelings of powerlessness (Abalakina‐Paap et al, ; Pratt, ; Zarefsky, 1984/), anxiety (Grzesiak‐Feldman, ; Radnitz & Underwood, ), anxious attachment style (Green & Douglas, ), and existential anxiety (Newheiser, Farias, & Tausch, ). Further, Bruder et al () demonstrated a relationship between conspiracy thinking and low feelings of control in the sociopolitical domain (see also Nyhan, ; van Prooijen and Acker ; Uscinski & Parent, ).…”
Section: Definitionsmentioning
confidence: 90%
“…Various scholars view conspiracy theories as results of people’s and groups’ attempts to understand social and political reality (Radnitz & Underwood, ). For example, Knight () understands conspiracy theories as symptoms rather than causes of social dysfunction and proposes that conspiracy theories could be seen as a part of a class‐based alienation from contemporary neo‐liberalism (see also Knight, ).…”
Section: Definitionsmentioning
confidence: 99%
“…As the COVID-19 pandemic continues to spread, rumors about its emergence, possible treatments, and adequate prevention measures are rapidly circulating on social media and the news, some of which include conspiracy theories. A variety of conspiracy theories are tied to partisanship (Einstein & Glick, 2015;Hartman & Newmark, 2012;Pasek et al, 2015;Smallpage et al, 2017), for partisans are prone to believe stories accusing opposing groups (Miller & Saunders, 2016;Oliver & Wood, 2014;Radnitz & Underwood, 2015). Indeed, political partisanship has been found to have a significant effect on COVID-19 prevention measures (Farias & Pilati, 2020;Pennycook et al, 2020), risk perceptions (Pennycook et al, 2020), and misperceptions (Pennycook et al, 2020).…”
Section: Covid-19 Political Partisanship and Conspiracy Theoriesmentioning
confidence: 99%
“…For example, belief in conspiracy theories has been linked to factors such as non-clinical delusional thinking (Dagnall, Drinkwater, Parker, Denovan & Parton, 2015) and schizotypy (Barron, Morgan, Towell, Altemeyer & Swami, 2014;Darwin, Neave & Holmes, 2011;Bruder, Haffke, Neave, Nouripanah & Imhoff, 2013;van der Tempel & Alcock, 2015;Swami, Pietschnig, Tran, Nader, Stiener & Voracek, 2013). Furthermore, believers have been characterised as mistrustful (Goertzel, 1994), powerless, (Abalakina-Paap et al, 1999), uncertain (van Prooijen & Jostmann, 2013, and anxious (Grzesiak-Feldman, 2013;Radnitz & Underwood, 2017).…”
Section: Social Cognitionmentioning
confidence: 99%